On the Lebesgue Inequality on Classes of ψ -Differentiable Functions
We consider the deviations of Fourier sums in the spaces C^ψ . The estimates of these deviations are expressed via the best approximations of the ψ -derivatives of functions in the Stepanets sense. The sequences ψ = (ψ_1, ψ_2) are quasiconvex., number=6, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Zaderei, N. N. and Zaderei, P. V., year=2013, month=Jun., pages=844–849